Penelitian Sejarah Sosial Media - Kartini, Kartini; Gultom, Nurhayati; Sari, Novita; Annisa, Adelia Nur (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study aims to find out that social media has now become a trend in marketing communications. Social Media is an online media, with its users can easily participate, share and create content including blogs, social networks, wikis, forums and virtual worlds. Blogs, social networks and wikis are the most common forms of social media used by people around the world. Some examples of social media that are currently developing are Instagram, Twitter, Line, Facebook, Youtube, and others. The use of social media as one of the most important promotional media. Most Indonesian people have made social media part of their lifestyle. Advances in science and technology, especially the internet, have changed the way people communicate from one to many to many to many. Keywords: history, social media